Competitive programming: A teaching methodology analysis applied to first-year programming classes - Bandeira, Ian Nery; Machado, Thiago Veras; Dullens, Vitor F.; Canedo, Edna Dias (Proceedings - Frontiers in Education Conference, 2019)
The Brazilian education methodology follows a very traditional pattern in the middle and high school years. Although it is very difficult to measure the degree of study between particular and public schools, the first-year university students face many difficulties between the clash of very different teaching learning methods. This paper presents an analysis of Competitive Programming, a non-traditional approach based on the Algorithm Problem Solving method, applied to teaching first-year programming classes for the Computer Science course at the University of Brasília (UnB). The main goal is to analyze if there is any correlation between the different teaching methods applied to this specific subject and an increased proficiency toward abilities that are useful not merely to programming, but also to group related projects in their future, such as proactivity and familiarity towards programming logic. The leading method of data acquiring was utilizing a questionnaire and the analysis by data provided by teachers, which brought an in-depth exploration about a disparity between the student's difficulty towards more advanced subjects when introduced with the two different teaching methods, and an improvement in both student's proactivity and familiarity regarding programming.